Eco-friendly machining of T6061 aluminium alloy using titanium carbonitride (TiCN) coated tools - Mohamed Ariff, Tasnim Firdaus; Sabiyah, Mohamad Yazid; Adam, Mohd Amirul; Nor, Mohd Anuar (Trans Tech Publications, Switzerland, 2012)
Traditional wet machining methods using oil based cutting fluids and water based cutting fluids are currently being used widely in the industry. Since oil based cutting fluids contributes to environmental problems, water based cutting fluids were introduced to minimize these effects even though not extensively used everywhere in all parts of the world. Eco-friendly machining is introduced for making the environment a better and healthier place by reducing the amount of contaminants and pollution into the water system. Two biodegradable cutting fluids have been chosen in this study; vegetable oil (palm oil) and water based cutting fluids. The wear behavior of TiCN coated tools is studied for three different cutting speeds (333, 415 and 517 m/min) and at two different cutting parameters; depth-of-cut, d and feed rate, f (d = 0.2 mm, f = 0.4 mm/rev and d = 0.4 mm, f = 0.6 mm/rev). Wear rate for machining using palm oil cutting fluid is lower (longer tool life) than the wear rate obtained from using water based coolants. Palm oil has better lubrication properties compared to water based coolants which have better cooling effects. The optimum cutting parameters for machining T6061 Aluminium alloy using TiCN coated tool is found; 333 m/min (water based) and 415 m/min (palm oil) at a depth of cut of 0.4 mm and feed rate of 0.6 mm/rev.